Overexpression of a CPYC-Type Glutaredoxin, OsGrxC2.2, Causes Abnormal Embryos and an Increased Grain Weight in Rice - Liu, Shengjie; Fu, Hua; Jiang, Jieming; Chen, Zhongjian; Gao, Jiadong; Shu, Haoran; Zhang, Sheng; Yang, Chengwei; Liu, Jun (Frontiers in Plant Science, 2019)
Glutaredoxins (Grxs) are a ubiquitous group of oxidoreductase enzymes that are important in plant growth and development; however, the functions of rice Grxs have not been fully elucidated. In this paper, we showed that one of the Grxs, encoded by OsGrxC2.2, exhibited Grx activity. Furthermore, we demonstrated that OsGrxC2.2 was able to regulate embryo development during embryogenesis. Transgenic rice lines overexpressing OsGrxC2.2 unexpectedly exhibited degenerate embryos as well as embryoless seeds. Our data indicated that the embryonic abnormalities occurred at an early stage during embryogenesis. We found that the expression of several endodermal layer marker genes for embryo development, such as OSH1 (apical region marker), OsSCR (L2 ground tissue marker), and OsPNH1 (L3 vascular tissue marker), were significantly decreased in the OsGrxC2.2-overexpressed transgenic rice lines. In contrast, the transcript levels of the majority of protodermal layer markers, including HAZ1, ROC2, ROC3, and RAmy1A, and the shoot apical meristem marker HB, showed little change between the wild-type (WT) and OsGrxC2.2-overexpressing embryos. Surprisingly, the seed weight of the overexpressed transgenic rice was remarkably increased in comparison to that of the WT. These results indicate that the overexpression of OsGrxC2.2 interferes with the normal embryogenesis of rice embryos and leads to increased grain weight. To the best of our knowledge, this is the first report that OsGrxC2.2 is a rice embryo development-associated gene.